H2O2 self-supplied iron-copper bimetallic nano-enzyme as well as preparation method and application of H2O2 self-supplied iron-copper bimetallic nano-enzyme

By preparing iron-copper bimetallic nanozymes rich in peroxide bonds, and utilizing the synergistic catalysis of mesoporous silica carrier and iron-copper bimetallic ions to generate •OH from H2O2, the problems of insufficient H2O2 generation and poor stability in tumor treatment were solved, achieving efficient tumor cell killing and reducing side effects.

CN121016749APending Publication Date: 2025-11-28NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511224743.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing nanozymes in tumor treatment suffer from problems such as insufficient H2O2 generation, poor stability, and insufficient targeting, resulting in poor therapeutic effects and significant side effects.

Method used

Using mesoporous silica as a carrier, iron-copper bimetallic nanozymes rich in peroxide bonds were prepared by hydrothermal and low-temperature calcination methods. The iron-copper bimetallic ions synergistically catalyze the generation of highly cytotoxic •OH from H2O2, and the active ingredients are released in a controlled manner by degrading in the acidic environment of tumors in combination with the framework of mesoporous silica.

Benefits of technology

It achieves autonomous supply and efficient catalysis of H2O2, improves the generation efficiency of ROS, enhances the killing effect on tumor cells, and reduces the risk of damage to normal tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016749A_ABST
    Figure CN121016749A_ABST
Patent Text Reader

Abstract

The invention provides H2O2 self-supplied iron-copper bimetallic nano-enzyme and a preparation method and application thereof.The preparation method includes the steps that mesoporous silica serves as a carrier, copper nitrate trihydrate serves as a copper source, iron acetylacetonate serves as an iron source, reaction is conducted for 6 h under the hydrothermal condition, iron-copper double-doped mesoporous silica is synthesized, then the mesoporous silica is calcined for 3 h at the temperature of 500 DEG C in a muffle furnace, and the iron-copper bimetallic nano-enzyme is obtained. Under the alkaline condition provided by sodium hydroxide, a product obtained after calcination is subjected to H2O2 in-situ oxidation, and the iron-copper bimetallic nano-enzyme (O < 22->-Fe / Cu-O-Si) rich in peroxide bonds is prepared. The nano-enzyme has relatively strong H2O2 self-supply capability, and can be used for pointedly relieving the problems that the content of endogenous H2O2 in tumor cells is insufficient, and active oxygen is difficult to effectively generate. In a weakly acidic tumor microenvironment, the nano-enzyme can generate H2O2 and release low-valence iron and copper ions, the H2O2 is efficiently catalyzed to generate hydroxyl free radicals (OH) with high cytotoxicity through an iron-copper bimetal synergistic mediated Fenton-like reaction, the intracellular active oxygen level is greatly improved, and tumor cell apoptosis is effectively induced. SiO2 is used as a carrier, so that the stability and the biocompatibility of the material are improved, and the acid response controllable release of the active component at a tumor part is also realized. Through the synergistic effect of self-supply H2O2 and explosive OH generation, the dependence of traditional nano enzyme on exogenous H2O2 is overcome, and a new strategy is provided for tumor catalytic treatment.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of nanoscale enzyme preparation, and particularly relates to an H2O2 self-supplying iron-copper bimetallic nanoscale enzyme, a preparation method and application thereof. BACKGROUND

[0002] Cancer is a serious threat to human health, which is caused by abnormal cell genes or external environmental imbalance, leading to the transformation of normal cells into cancer cells. At present, surgery, chemotherapy and radiotherapy are the main treatment methods, among which surgery and radiotherapy have significant effects in early treatment, while small molecule chemotherapy drugs (such as camptothecin) are used for adjuvant therapy in the middle and late stages. These drugs enter the body through oral or intravenous routes, target the lesion through blood circulation, but have problems such as poor water solubility, short circulation period and rapid metabolism in the body, which makes it difficult to maintain the treatment effect. Non-specific mechanism of action makes it widely distributed in the body, not only causing insufficient drug concentration in tumor sites and reducing anti-tumor effect, but also significantly increasing the risk of systemic side effects. The progress of nanotechnology brings new opportunities for tumor treatment. Nanomaterials have high permeability and long retention (EPR) effect, and can penetrate and stay in the tumor for a long time compared with traditional small molecule drugs. Combined with the modification of targeting ligands, it can also promote the active targeting accumulation of the drug at the lesion. Artificial enzymes based on nanomaterials are called “nanoscale enzymes”, which have adjustable enzyme catalytic activity, high physiological stability, easy preparation and low cost, and have great application potential in the field of biomedicine. In the treatment of tumors, the core advantage of nanoscale enzymes is to produce reactive oxygen species (ROS) to kill tumor cells. ROS, as a class of oxygen molecules with high chemical reactivity, can destroy biological macromolecules such as lipids, proteins and DNA in tumor cells, thereby inducing tumor cell apoptosis or necrosis. Taking the nanoscale enzyme simulating peroxidase as an example, it can efficiently simulate the catalytic function of natural peroxidase, and in the presence of hydrogen peroxide (H2O2), it can decompose and convert H2O2 into hydroxyl radicals (•OH). As an important member of ROS, •OH has strong oxidizing ability and high cytotoxicity, which can rapidly react with various biological molecules in tumor cells, causing irreversible damage to cell structure and function, and thus achieving the purpose of eliminating tumor cells. Although the content of H2O2 in tumor tissue is higher than that in normal cells, it is still not enough to continuously and effectively produce ROS. At present, many studies have focused on increasing the level of H2O2 in tumors to solve the problem of insufficient endogenous H2O2. The strategy of loading glucose oxidase (GOx) to catalyze the oxidation of intratumoral glucose to generate H2O2 in situ has made great progress. However, the hypoxic environment of tumor leads to limited catalytic efficiency of GOx. Therefore, the development of nanoscale enzymes that do not require external energy input and can achieve self-supply of H2O2 has become an important research direction in tumor treatment. Recently, a variety of metal peroxide nanoparticles such as copper peroxide (CuO2), calcium peroxide (CaO2), magnesium peroxide (MgO2), zinc peroxide (ZnO2) and barium peroxide (BaO2) have attracted widespread attention of researchers because they have been explored for cancer treatment, antibacterial and tissue regeneration.Metal peroxides have excellent performance, can produce H2O2 under the condition of micro-acid or water in vivo and in vitro, mediate Fenton-like reaction under appropriate conditions, catalyze H2O2 to convert into strong oxidizing •OH, and enhance the killing ability of ROS. In particular, iron ions (Fe. 2+ ) with strong Fenton catalytic activity, copper ions (Cu 2+ ) with Fenton-like catalytic activity and materials with self-supplying H2O2 ability are combined to form a specific composite system, which can synergistically enhance the generation efficiency of ROS and the tumor killing effect. However, metal peroxides are unstable, they are easy to react with water in physiological environment, easy to decompose in blood circulation, produce H2O2 and release metal ions in advance, reduce the efficiency of targeting tumor microenvironment, and may also damage normal tissues. The stability needs to be improved through surface modification or nano-carrier encapsulation to ensure precise delivery to tumor sites. Mesoporous silica nanomaterials have unique pore structure, large specific surface area and easily modified surface, and have good biocompatibility and non-toxicity, which are ideal nanomaterials for biomedical field. In addition, the SiO2 skeleton can protect the material to stably exist in the blood circulation, and only under the acidic conditions of the tumor, the active ingredients can be released by skeleton degradation to achieve controlled release, thereby improving the treatment accuracy and safety.

[0003] Therefore, in-situ construction of iron-copper bimetallic nanoscale enzyme rich in peroxide bond in SiO2 skeleton is a strategy that is expected to realize self-sufficient H2O2 and efficient catalysis of H2O2 to generate high cytotoxicity ROS, which can achieve efficient killing of tumor cells. Therefore, it is very necessary to construct a metal peroxide nanomedicine carrier based on this strategy for tumor treatment. SUMMARY

[0004] The purpose of the present application is to provide a H2O2 self-supplying iron-copper bimetallic nanoscale enzyme, a preparation method and applications thereof.

[0005] In order to achieve the above purpose, the technical scheme adopted by the present application is as follows:

[0006] A preparation method of a H2O2 self-supplying iron-copper bimetallic nanoscale enzyme, comprising the following steps:

[0007] S1, preparing mesoporous silica;

[0008] S2, preparing iron-copper doped silicon-based nanoscale enzyme (Fe / Cu-O-Si) by hydrothermal and low-temperature calcination method;

[0009] S3, preparing iron-copper bimetallic nanoscale enzyme rich in peroxide bond (O2 2- -Fe / Cu-O-Si).

[0010] 1. Preferably, the mesoporous silica in step S1 is prepared with tetraethyl orthosilicate as the silicon source, ammonium cetyltrimethyl p-toluenesulfonate as the surfactant, the addition of triethanolamine and 1-butyl-3-methyl imidazole trifluoromethanesulfonate. The addition amount is respectively: 7-16 mL of tetraethyl orthosilicate, 0.8-2 g of ammonium cetyltrimethyl p-toluenesulfonate; 0.1-0.4 g of triethanolamine and 10-20 mg of 1-butyl-3-methyl imidazole trifluoromethanesulfonate. After mixing the above substances, stirring reaction is carried out at 80-100℃ for 2-3h, and then the product is centrifuged and washed with anhydrous ethanol; the white solid powder obtained is the mesoporous silica.

[0011] 2. Preferably, step S2 specifically includes: adding 80-200 mg of copper nitrate trihydrate, 10-22 mg of acetylacetone iron, 0.5-1.1 g of ammonium chloride and 1.6-2.4 g of urea in 50-100 mg of mesoporous silica, and stirring uniformly to obtain a mixed solution system; the above solution is sealed in an autoclave, and kept at 200-220℃ for 5-8h; after the autoclave is naturally cooled to room temperature, the obtained product is washed and centrifuged and dried to completely remove residual metal ions, and then the sample is placed in a muffle furnace, calcined at 400-500℃ for 3-4h to finally obtain a light orange solid powder, which is Fe / Cu-O-Si.

[0012] 3. Preferably, step S3 specifically includes: dispersing 10-20 mg of Fe / Cu-O-Si in 10-20 mL of deionized water, adding 5-10 mL of sodium hydroxide solution, 100-200 μL of H2O2, stirring at room temperature for 30-50 min, centrifuging and washing with ethanol for 3 times, and freeze-drying. The obtained dark yellow solid powder is O2 2- -Fe / Cu-O-Si.

[0013] Another object of the present application is to provide a preparation method of an H2O2 self-supplying iron-copper bimetallic nanoscale enzyme, denoted as O2 2- -Fe / Cu-O-Si.

[0014] The last object of the present application is to provide the application of the in-situ derived iron-copper bimetallic nanoscale enzyme rich in peroxide bond in self-production of H2O2 and enzyme catalytic performance.

[0015] The beneficial effects of the present application are:

[0016] This invention provides a method for preparing a self-supplied H2O2 iron-copper bimetallic nanozyme and its application in the field of tumor catalytic therapy. Mesoporous silica is used as a carrier, copper nitrate trihydrate as the copper source, and iron acetylacetone as the iron source. The hydrothermal reaction is carried out for 6 hours, and the resulting solid is calcined in a muffle furnace at 500°C for 3 hours. The calcined sample is then subjected to in-situ oxidation with H2O2 under alkaline conditions provided by sodium hydroxide to successfully prepare a peroxy bond-rich iron-copper bimetallic nanozyme. The designed nanozyme exhibits high peroxidase-like activity and excellent self-supplied H2O2 capability. Through the synergistic catalysis of iron-copper bimetallic ions, H2O2 generates •OH, further increasing ROS levels and inducing tumor cell apoptosis. Attached Figure Description

[0017] Figure 1 The image is a transmission electron microscope image of mesoporous silica provided in Example 1;

[0018] Figure 2 The O2 prepared in Example 1 2- Transmission electron microscope image of Fe / Cu-O-Si;

[0019] Figure 3 The O2 prepared in Example 1 2- -Fe / Cu-O-Si corresponding elemental mapping image;

[0020] Figure 4 The O2 prepared in Example 1 2- Nitrogen adsorption and desorption curves of Fe / Cu-O-Si;

[0021] Figure 5 The O2 prepared in Example 1 2- Pore ​​size distribution curve of Fe / Cu-O-Si;

[0022] Figure 6 The O2 prepared in Example 1 2- Enzyme catalytic performance test of Fe / Cu-O-Si;

[0023] Figure 7 The O2 prepared in Example 1 2- H2O2 generation curve of titanium sulfate with Fe / Cu-O-Si. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0025] Example 1

[0026] This embodiment provides a self-supplied H2O2 iron-copper bimetallic nanozyme, and the preparation method includes the following steps:

[0027] (1) Preparation of mesoporous silica (mSiO2): First, 0.96 g (2.4 mmol) of hexadecyltrimethyl-p-toluenesulfonate, 0.168 g (1.1 mmol) of triethanolamine and 10 mg (0.03 mmol) of 1-butyl-3-methylimidazolium trifluoromethanesulfonate were mixed in 50 mL of deionized water and stirred at 80 °C for 1 h. Then, 7.8 mL (35 mmol) of tetraethyl orthosilicate was rapidly added to the mixture, and the mixture was stirred at 80 °C for another 1 h. The product was then centrifuged at 8000 r / min for 5 min and washed twice with anhydrous ethanol and water, respectively. The resulting white solid powder was mSiO2.

[0028] The structure of the prepared mSiO2 was confirmed by observation using a transmission electron microscope. Figure 1 It can be seen that the particle size of mSiO2 is about 110 nm, and the mSiO2 has a distinct dendritic structure and uniform particle size distribution.

[0029] (2) Preparation of iron-copper doped silicon-based nanozyme (Fe / Cu-O-Si): 50 mg of mSiO2 was dispersed in 20 mL of deionized water, 96 mg (0.4 mmol) of copper nitrate trihydrate and 11 mg (0.03 mmol) of ferric acetylacetone were added, and the mixture was sonicated for 15 min to form solution A. 535 mg (10 mmol) of ammonium chloride was dissolved in 10 mL of deionized water, and 1.62 g (27 mmol) of urea was added. The mixture was sonicated for 15 min to form solution B. Solutions A and B were mixed and stirred for 30 min, transferred to a high-pressure reactor, and reacted at 200 °C for 6 h. After cooling to room temperature, the obtained product was washed and centrifuged to dry. The obtained sample powder was placed in a muffle furnace and calcined at 500 °C for 3 h. The resulting light orange solid powder was Fe / Cu-O-Si.

[0030] (3) Iron-copper bimetallic nanozymes rich in peroxy bonds (O2) 2- Preparation of Fe / Cu-O-Si: 10 mg of Fe / Cu-O-Si was dispersed in 10 mL of deionized water, 5 mL of sodium hydroxide solution (0.02 M) was added, and the mixture was stirred for 3 min. Then, 100 μL of H₂O₂ was added, and the mixture was stirred at room temperature for 30 min. The mixture was centrifuged, washed three times with ethanol, and lyophilized. The resulting deep yellow solid powder was O₂. 2- -Fe / Cu-O-Si.

[0031] like Figure 2 As shown, O2 was observed using a transmission electron microscope.2- Fe / Cu-O-Si nanoszyme was characterized by morphology, and it can be seen from the figure that O2 2- Fe / Cu-O-Si nanoszyme is a spherical structure, the particle size is uniform and the particle size is about 100 nm.

[0032] Figure 3 Fe / Cu-O-Si nanoszyme is a spherical structure, the particle size is uniform and the particle size is about 100 nm. 2- Fe / Cu-O-Si nanoszyme was characterized by elemental mapping, and it can be seen from the figure that copper and iron elements are uniformly distributed on the nanoparticles.

[0033] Fe / Cu-O-Si nanoszyme was characterized by elemental mapping, and it can be seen from the figure that copper and iron elements are uniformly distributed on the nanoparticles. 2- Fe / Cu-O-Si nanoszyme was subjected to nitrogen adsorption and desorption test, and the results are shown in Figure 4 Fe / Cu-O-Si nanoszyme was subjected to nitrogen adsorption and desorption test, and the results are shown in 2- Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m 2 / g; Figure 5 Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m 2- Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m

[0034] Figure 6 Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m 2- Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m 2- Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m

[0035] Figure 7 Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m 2- Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m 2- Fe / Cu-O-Si nanoszyme has a specific surface area of 452.6 m

[0036] Example 2

[0037] The present embodiment provides a H2O2 self-supplying iron-copper bimetallic nanoszyme and a preparation method comprising the following steps:

[0038] (1) Preparation of mesoporous silica (mSiO2): First, 1.44 g (3.6 mmol) of cetyltrimethylammonium p-toluenesulfonate, 0.252 g (1.69 mmol) of triethanolamine and 15 mg (0.04 mmol) of 1-butyl-3-methylimidazolium trifluoromethanesulfonate were mixed in 75 mL of deionized water and stirred at 80°C for 1 h. Then, 11.7 mL (52.5 mmol) of tetraethyl orthosilicate was quickly added to the mixture, and after stirring at 80°C for another 1 h, the product was centrifuged at 8000 r / min for 5 min and washed twice with anhydrous ethanol and water, respectively. The white solid powder obtained was mSiO2.

[0039] (2) Preparation of iron-copper doped silicon-based nanoscale enzyme (Fe / Cu-O-Si): 75 mg of mSiO2 was dispersed in 30 mL of deionized water, 144 mg (0.6 mmol) of copper nitrate trihydrate and 16.5 mg (0.048 mmol) of iron acetylacetone were added, and ultrasonic was performed for 15 min to form solution A. 803 mg (15 mmol) of ammonium chloride was dissolved in 15 mL of deionized water, and 2.43 g (40.5 mmol) of urea was further added, and ultrasonic was performed for 15 min to form solution B. After mixing A and B solutions, stirring was performed for 30 min. The above solution was transferred to a high-pressure reaction kettle, and kept at 200°C for 6 h. After the high-pressure reaction kettle was naturally cooled to room temperature, the obtained product was washed and centrifuged and dried to completely remove residual metal ions. Then, the sample powder was placed in a muffle furnace and calcined at 500°C for 3 h. The obtained light orange solid powder was Fe / Cu-O-Si.

[0040] (3) Preparation of iron-copper bimetallic nanoscale enzyme (O2 2- -Fe / Cu-O-Si) rich in peroxide bonds: 15 mg of Fe / Cu-O-Si was dispersed in 15 mL of deionized water, 7.5 mL of sodium hydroxide solution (0.02 M) was added and stirred for 3 min, then 150 μL of H2O2 was further added, and stirred at room temperature for 30 min. After centrifugation and washing with ethanol for 3 times, freeze-drying was performed. The obtained dark yellow solid powder was O2 2- -Fe / Cu-O-Si.

[0041] Example 3

[0042] The present embodiment provides an iron-copper bimetallic nanoscale enzyme with H2O2 self-supply, and a preparation method comprising the following steps:

[0043] (1) Preparation of mesoporous silica (mSiO2): first, 1.92 g (4.8 mmol) of cetyltrimethylammonium p-toluenesulfonate, 0.336 g (2.26 mmol) of triethanolamine and 20 mg (0.066 mmol) of 1-butyl-3-methylimidazolium trifluoromethanesulfonate were mixed in 100 mL of deionized water, and stirred at 80°C for 1 h. Then, 15.6 mL (70 mmol) of tetraethyl orthosilicate was quickly added to the mixture, and the reaction was stirred at 80°C for another 1 h. The product was centrifuged at 8000 r / min for 5 min and washed with anhydrous ethanol and water twice. The obtained white solid powder was mSiO2.

[0044] (2) Preparation of iron-copper doped silicon-based nanoscale enzyme (Fe / Cu-O-Si): 100 mg of mSiO2 was dispersed in 40 mL of deionized water, 192 mg (0.8 mmol) of copper nitrate trihydrate and 22 mg (0.062 mmol) of iron acetylacetone were added, and ultrasonic was performed for 15 min to form solution A. 1.07 g (20 mmol) of ammonium chloride was dissolved in 20 mL of deionized water, and 3.24 g (54 mmol) of urea was further added. After stirring, ultrasonic was performed for 15 min to form solution B. The A and B solutions were mixed and stirred for 30 min, transferred to a high-pressure reaction kettle, and reacted at 200°C for 6 h. After cooling to room temperature, the obtained product was washed and centrifuged and dried. The obtained sample powder was calcined at 500°C for 3 h in a muffle furnace, and the obtained light orange solid powder was Fe / Cu-O-Si.

[0045] (3) Preparation of iron-copper bimetallic nanoscale enzyme (O2 2- -Fe / Cu-O-Si) rich in peroxide bonds: 20 mg of Fe / Cu-O-Si was dispersed in 20 mL of deionized water, 10 mL of sodium hydroxide solution (0.02 M) was added and stirred for 3 min, and 200 μL of H2O2 was further added. After stirring at room temperature for 30 min, centrifugation and ethanol washing were performed for 3 times, and freeze-drying was performed. The obtained dark yellow solid powder was O2 2- -Fe / Cu-O-Si.

[0046] By adopting the above technical solutions disclosed in the present application, the following beneficial effects are obtained:

[0047] The application discloses an H2O2 self-supplying iron-copper bimetal nanoscale enzyme, a preparation method and application thereof. The nanoscale enzyme has many excellent characteristics: first, the synthesis process is simplified, large-scale preparation is easy, and the raw material cost is low. Moreover, the generated nanoscale enzyme has uniform particle size distribution and good dispersibility. Second, the nanoscale enzyme has strong self-supplying H2O2 capacity, and can solve the problem that tumor cells are difficult to continuously and effectively generate ROS due to insufficient endogenous H2O2 content. Third, the prepared nanoscale enzyme has high peroxidase-like activity, generates •OH by catalyzing H2O2, further improves the ROS level, and induces cell apoptosis. Fourth, the iron-copper bimetal nanoscale enzyme rich in peroxide bonds releases Cu 2+ , Fe 2+ / Fe 3+ and H2O2 in an acidic environment. The released Fe 2+ can efficiently catalyze the Fenton reaction of H2O2 to directly generate highly toxic •OH; at the same time, Cu 2+ can be reduced to Cu + by endogenous reducing substances in the tumor microenvironment, and then catalyze H2O2 to generate additional •OH through a Fenton-like reaction, significantly amplifying the generation efficiency of •OH. Fifth, the prepared nanoscale enzyme can degrade in response to the tumor microenvironment, which can improve the biological safety on the one hand, and the Fenton / Fenton-like reaction of the degraded metal ions can enhance the treatment effect on the other hand.

[0048] The above only describes the preferred embodiments of the application, and it should be pointed out that, for ordinary skilled in the art, without departing from the principles of the application, a number of improvements and refinements can be made, and these improvements and refinements should be considered as the protection scope of the application.

Claims

1. A method for preparing an H2O2 self-supplying iron-copper bimetallic nanoszyme, characterized in that, The chemical formula is: O2 2- - Fe / Cu-O-Si.

2. A method for preparing an H2O2 self-supplying iron-copper bimetallic nanoszyme, characterized in that, Comprising the following steps: S1, mesoporous silica (mSiO2) is prepared by microemulsion method; S2, using mSiO2 prepared in step S1 as raw material, iron and copper doped silicon-based nanoscale enzyme (Fe / Cu-O-Si) is prepared by hydrothermal and low temperature calcination method; S3, using Fe / Cu-O-Si prepared in step S2 as raw material, and under alkaline conditions provided by sodium hydroxide, an iron-copper bimetallic nanoscale enzyme rich in peroxide bonds (O2 2- -Fe / Cu-O-Si) is prepared by an in-situ oxidation method with H2O2.

3. The method for preparing a self-supplied H2O2 iron-copper bimetallic nanozyme according to claim 1, characterized in that, The mSiO2 in step S1 uses tetraethyl orthosilicate as a silicon source, ammonium cetyltrimethyl p-toluenesulfonate as a surfactant, adds triethanolamine and 1-butyl-3-methyl imidazole trifluoromethanesulfonate, mixes the above substances, stirs and reacts at 80-100 DEG C for 2-3 h, then centrifugally separates and washes the product with anhydrous ethanol; the white solid powder obtained is mesoporous silica, denoted as mSiO2.

4. The method for preparing a self-supplied H2O2 iron-copper bimetallic nanozyme according to claim 1, characterized in that, The preparation of the iron and copper doped silicon-based nanoscale enzyme (Fe / Cu-O-Si) in step S2, first disperses mSiO2 in deionized water, adds copper nitrate trihydrate and acetylacetone iron to obtain solution A; dissolves ammonium chloride in deionized water, stirs and ultrasonically obtains solution B; mixes A and B and stirs, transfers into a high-pressure reaction kettle and reacts for 6-8 h, cools, then solid powder is calcined in a muffle furnace for 3-5 h, to obtain light orange solid powder as iron and copper doped silicon-based nanoscale enzyme, denoted as Fe / Cu-O-Si.

5. The method for preparing a self-supplied H2O2 iron-copper bimetallic nanozyme according to claim 1, characterized in that, Preparation of the iron-copper bimetallic nanoszyme rich in peroxide bonds (O2 2- -Fe / Cu-O-Si): Fe / Cu-O-Si was dispersed in deionized water, sodium hydroxide solution, H2O2 was added, after stirring at room temperature, centrifugation, ethanol washing, freeze-drying, the dark yellow solid powder was obtained as the iron-copper bimetallic nanoszyme rich in peroxide bonds, marked as O2 2- -Fe / Cu-O-Si.

6. The method for preparing a self-supplied H2O2 iron-copper bimetallic nanozyme according to claim 2, characterized in that, The specific steps of step S1 include: ammonium cetyltrimethyl p-toluenesulfonate is used as a surfactant, triethanolamine and 1-butyl-3-methyl imidazole trifluoromethanesulfonate are added. The addition amounts are respectively: 7-16 mL of tetraethyl orthosilicate, 0.8-2 g of ammonium cetyltrimethyl p-toluenesulfonate; 0.1-0.4 g of triethanolamine and 10-20 mg of 1-butyl-3-methyl imidazole trifluoromethanesulfonate. The above substances are mixed, stirred and reacted at 80-100 DEG C for 2-3 h, then the product is centrifugally separated and washed with anhydrous ethanol; the white solid powder obtained is mSiO2.

7. The method for preparing a self-supplied H2O2 iron-copper bimetallic nanozyme according to claim 2, characterized in that, The specific steps of step S2 include: 50-100 mg of mesoporous silica is added with 80-200 mg of copper nitrate trihydrate, 10-22 mg of acetylacetone iron, 0.5-1.1 g of ammonium chloride and 1.6-2.4 g of urea, stirs uniformly to obtain a mixed solution system; the above solution is sealed in a high-pressure kettle and kept at 200-220 DEG C for 5-8 h; after the high-pressure reaction kettle is naturally cooled to room temperature, the obtained product is washed, centrifugally dried to completely remove residual metal ions, then the sample is placed in a muffle furnace and calcined at 400-500 DEG C for 3-4 h to finally obtain light orange solid powder as Fe / Cu-O-Si.

8. The method for preparing a self-supplied H2O2 iron-copper bimetallic nanozyme according to claim 2, characterized in that, Step S3 specifically comprises: taking 10-20 mg of Fe / Cu-O-Si and dispersing it in 10-20 mL of deionized water, adding 5-10 mL of sodium hydroxide solution, 100-200 μL of H2O2, stirring at room temperature for 30-50 min, centrifuging and washing with ethanol for 3 times, freeze-drying, and the obtained dark yellow solid powder is O2 2- - Fe / Cu-O-Si.

9. A preparation method of an H2O2 self-supplying iron and copper bimetallic nanoscale enzyme prepared by the preparation method of any one of claims 2-8.

10. The use of the H2O2 self-supplying iron and copper bimetallic nanoscale enzyme of claim 9 in targeted tumor catalytic treatment.